Politeness Strategies in The Interview Between Taylor Swift and Jimmy Fallon - Rendra, Rizki Putra; Handayani, Nurma Dhona (PROJECT (Professional Journal of English Education), 2026)
This research employs a descriptive qualitative design to analyze the politeness strategies used in the interview between Taylor Swift and Jimmy Fallon on The Tonight Show. The study aims to explore how these strategies help maintain rapport and manage social dynamics between the speakers. Data was collected from the interview transcript, focusing on four politeness strategies outlined by Brown and Levinson (1987): bald on record, positive politeness, negative politeness, and off-record strategies. The data collection process involved transcribing the interview, identifying politeness strategies, and categorizing the utterances accordingly. For data analysis, the pragmatic identity method and the equalizing technique were applied, allowing the researcher to examine how the speakers manage social identity and maintain balance in the interaction. The findings revealed the frequency of each strategy: positive politeness was used 16 times, off-record strategies appeared 7 times, negative politeness was observed 6 times, and bald on record was used 3 times. These results show that positive politeness was the most frequent strategy, underscoring its importance in fostering solidarity and rapport in media conversations.